“A good method of making money?” : Seasonal Wilderness Guides` wellbeing in Finnish Lapland - Penttonen, Silja (fi=Lapin yliopisto|en=University of Lapland|, 2018)
Tourism is growing in Finnish Lapland and a major part of tourism is strongly focused on the winter season which usually runs from November or December until the following April. The tourism field provides a lot of seasonal-based employment in wintertime and seasonal income is a big motivator for these employees. Working conditions and wellbeing of these seasonal employees are an important topic in the growing field of tourism at the moment, and we need to be made more aware of this. In Lapland there is a growing need for foreign employees, but also for qualified employees. The seasonal labor employees often go through very tough outdoor working conditions and can endure extreme arctic winter weather in Lapland. Because the tourism field in Finnish Lapland is so diverse and wide ranging, I have chosen to focus my study on foreign wintertime wilderness guides who hold the Wilderness guide degree. In this research paper, I intend to focus on the working conditions and rights of these foreign employees and to discover their wellbeing, motivation and satisfaction. I aim to find out what are the main things affecting the wilderness guides` wellbeing during the winter season and how do they maintain their wellbeing throughout the season. The Frederick Herzberg`s Two-Factor Theory of work motivation is used as the theoretical framework and completed with the emotional labor view by Arlie Russell Hochschild. Erik Allardt`s wellbeing perspective is used to have a closer look at the wellbeing. Literature consists of written documents and research that is mostly published by the University of Lapland. The primary qualitative data consists of five semi-structured interviews which were done before the winter season 2017-2018 and five thematic interviews which were done afterwards in the summer of 2018. Seven professional foreign wilderness guides were interviewed and three of them participated for both interviews. The research results show that Herzberg’s theory held true for most of these topics and work required strong ...